Solution-Processable BODIPY-Based Small Molecules for Semiconducting Microfibers in Organic Thin-Film Transistors - Ozdemir, Mehmet; Choi, Donghee; Kwon, Guhyun; Zorlu, Yunus; Cosut, Bunyemin; Kim, Hyekyoung; Facchetti, Antonio (Amer Chemical Soc, 2016)
Electron-deficient pi-conjugated small molecules can function as electron-transporting semiconductors in various optoelectronic applications. Despite their unique structural, optical, and electronic properties, the development of BODIPY-based organic semiconductors has lagged behind that of other pi-deficient units. Here, we report the design and synthesis of two novel solution-proccessable BODIPY-based small molecules (BDY-3T-BDY and BDY-4T-BDY) for organic thin-film transistors (OTFTs). The new semiconductors were fully characterized by H-1/C-13 NMR, mass spectrometry, cyclic voltammetry, UV-vis spectroscopy, photoluminescence, differential scanning calorimetry, and thermogravimetric analysis. The single-crystal X-ray diffraction (XRD) characterization of a key intermediate reveals crucial structural properties. Solution-sheared top-contact/bottom-gate OTFTs exhibited electron mobilities up to 0.01 cm(2)/V center dot s and current on/off ratios of >10(8). Film microstructural and morphological characterizations indicate the formation of relatively long (similar to 0.1 mm) and micrometer-sized (1-2 mu m) crystalline fibers for BDY-4T-BDY-based films along the shearing direction. Fiber-alignment-induced charge-transport anisotropy (mu?/mu approximate to 10) was observed, and higher mobilities were achieved when the microfibers were aligned along the conduction channel, which allows for efficient long-range charge-transport between source and drain electrodes. These OTFT performances are the highest reported to date for a BODIPY-based molecular semiconductor, and demonstrate that BODIPY is a promising building block for enabling solution-processed, electron-transporting semiconductor films.
Keywords: organic thin-film transistor; n-channel semiconductor; BODIPY; small molecule-based microfiber